Financial and monetary issues as the crisis unfolds - James K. Galbraith (Levy Economics Institute of Bard College, 2009)
A group of experts associated with the Economists for Peace and Security and the Initiative for Rethinking the Economy met recently in Paris to discuss financial and monetary issues; their viewpoints, summarized here by Senior Scholar James K. Galbraith, are largely at odds with the global political and economic establishment. Despite noting some success in averting a catastrophic collapse of liquidity and a decline in output, the Paris group was pessimistic that there would be sustained economic recovery and a return of high employment. There was general consensus that the precrisis financial system should not be restored, that reviving the financial sector first was not the way to revive the economy, and that governments should not pursue exit strategies that permit a return to the status quo. Rather, the crisis exposes the need for profound reform to meet a range of physical and social objectives.
Keywords: 330